(untitled) (Research, Society and Development, 2025)
Our aim is to present the protocol for a scoping review, guided by the question: "What does the literature report about education for teaching in undergraduate healthcare programs in Brazil?" The review will include scientific articles, theses, and dissertations published between 2018 and 2024, following the Joanna Briggs Institute (JBI) methodology and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR). Based on the PCC mnemonic, it will consider as the Population, publications on education for teaching in undergraduate healthcare programs [Physical Education, Nursing, Pharmacy, Physical Therapy, Speech Therapy, Medicine, Nutrition, Dentistry, Psychology, Social Work, Occupational Therapy, and Collective Health]; as the Concept, formative processes for educators and supervisors in higher education (undergraduate level); and as the Context, the Brazilian setting, with no language restrictions. After a pilot study, the initial search will be conducted in the following databases: Scielo, LILACS, CINAHL (EBSCO), Bdenf, SCOPUS, and BDTD, by two researchers, with inclusion/exclusion determined through analysis of titles, keywords, and abstracts. For data extraction from the full texts, an instrument developed according to JBI guidelines will be used. The database, organized in spreadsheets, will undergo quantitative and qualitative analysis by thematic similarity. The synthesis and final report will follow PRISMA-ScR. We hope to contribute to the mapping of education for teaching in healthcare in Brazil, as well as to the identification of gaps that may support the development of new practices and research.